1955
DOI: 10.1017/s0021859600040247
|View full text |Cite
|
Sign up to set email alerts
|

The growth of pigs kept to one level of feeding, in two environments, and fed diets with and without an antibiotic

Abstract: 1. Pigs housed in both a good and a bad piggery were kept to a medium plane of feeding on diets with and without a procaine penicillin supplement. Antibiotic improved neither efficiency nor rate of growth in either piggery during the period from weaning to 100 lb. live weight, nor from then to slaughter at 200 lb. live weight. The average temperatures during the first half of the experiment were 43 and 51° F. in the bad piggery and in the sleeping pens of the good piggery respectively. During the second half o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
0

Year Published

1956
1956
1960
1960

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…The overall increase in dressing percentage by the inclusion of antibiotics in the diet is in agreement with other research work (Lucas and Calder, 1955). However, the difference due to antibiotic feeding varies considerably among replicates although the variation in dressing percentage is negligible.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The overall increase in dressing percentage by the inclusion of antibiotics in the diet is in agreement with other research work (Lucas and Calder, 1955). However, the difference due to antibiotic feeding varies considerably among replicates although the variation in dressing percentage is negligible.…”
Section: Discussionsupporting
confidence: 91%
“…The magnitude of the increase in growth rate seems to be associated with the weight of the pigs when first fed antibiotics, a conclusion also reached by Lucas and Calder (1955). The magnitude of the increase in growth rate seems to be associated with the weight of the pigs when first fed antibiotics, a conclusion also reached by Lucas and Calder (1955).…”
Section: Discussionmentioning
confidence: 84%
“…The diets fed in our experiments all contained procaine penicillin, and in the discussion in a previous paper (Lucas & Calder, 19556) we noted that some reports from overseas indicate that the growth response to dietary antibiotic might be greater when the plane of feeding is high than when it is low, although reports from the United Kingdom do not so far support this. However, we suggested that more evidence is required on this point.…”
mentioning
confidence: 58%
“…1 and 2 supplements of procaine penicillin did not improve growth performance as much as supplements of copper sulphate. The effects of adding antibiotic to diets have varied considerably, and we have discussed some of the causes of this variation in a previous paper (Lucas & Calder, 19556). However, Exps.…”
Section: Discussionmentioning
confidence: 99%